Strategi Branding Gastronomi Kudapan Tradisional Bugis-Makassar pada Hotel Berbintang - Syahrial, Syahrial; Anjarsari, Hilda (CV. Social Politic Genius (SIGn), 2022)
This research aims to understand the gastronomic branding strategies of Bugis-Makassar traditional treats in starred hotels. This research uses an inductive qualitative analysis. Inductive analysis is an approach that begins with field facts, analyzes them based on relevant theories and arguments, and ultimately yields a conclusion. The results show that Bugis-Makassar traditional treats have been successfully positioned as a crucial element in the hospitality industry, particularly in South Sulawesi. The branding strategies implemented by several starred hotels involve aspects of nutrition, color, shape, layout, and the arrangement of slices that not only blend local wisdom with international standards but also highlight the originality and authenticity of the cuisine. The visually appealing and nutritionally compliant presentation, integrated with local wisdom in every aspect, demonstrates how Bugis-Makassar traditional treats can enhance the culinary experience offered by starred hotels, while also strengthening the identity of traditional gastronomy in a global context. Therefore, it is recommended that the relevant stakeholders expand the application of gastronomic branding strategies for Bugis-Makassar traditional treats. Chefs are encouraged to continue developing innovations in a presentation that include aspects of nutrition, colour, shape, layout, and the arrangement of slices to maintain and increase tourist interest in traditional treats. Tourists are urged to include traditional treats as a vital part of their travel experience. Cultural experts are expected to provide preferences for other types of Bugis-Makassar traditional treats that are being eroded or no longer found in the modern era to chefs so that they can be considered for revitalization and reintroduction in menus. Furthermore, this strategy can be applied not only in starred hotels but also in cultural events, culinary festivals, and other related sectors to enhance recognition and appreciation of Bugis-Makassar traditional treats on a broader scale.